Impact of Self-Worth Perception on Achievement Motivation among University Students - Samar Fahd; Fatima Khurram Bukhari; Kalsoom Akhtar; Umair Siddique; Fiza Javed (Journal of Management Practices, Humanities and Social Sciences, 2021)
The present research aims to highlight the impact of self-worth perception on achievement motivation among university students. The Sample, which was collected by the simple random sampling was consisted of 50 male and 79 female University students (N=129). The study is cross-sectional in nature. Two instruments were used to check self-worth and achievement motivation. One was Students’ Motivation scale and the other was Contingencies of self-worth scale. The results of the data, analyzed through the SPSS, showed that self-worth is significantly predicts and positively correlated with the achievement motivation of university students. Moreover, there was also a significant difference on the basis of gender. Results revealed that female students have high self-worth and academic motivation as compared to male students.